Immunogenicity of three doses of bivalent, trivalent, or type 1 monovalent oral poliovirus vaccines with a 2 week interval between doses in Bangladesh: an open-label, non-inferiority, randomised, controlled trial. Issue 8 (August 2015) - Estívariz, Concepción F; Anand, Abhijeet; Gary, Howard E; Rahman, Mahmudur; Islam, Jannatul; Bari, Tajul I; Wassilak, Steven G F; Chu, Susan Y; Weldon, William C; Pallansch, Mark A; Heffelfinger, James D; Luby, Stephen P; et al.
Summary Background The provision of several doses of monovalent type 1 oral poliovirus vaccine (mOPV1) and bivalent OPV1 and 3 (bOPV) vaccines through campaigns is essential to stop the circulation of remaining wild polioviruses. Our study aimed to assess the shortening of intervals between campaigns with bOPV and mOPV1 and to assess the immunogenicity of bOPV in routine immunisation schedules. Methods We did an open-label, non-inferiority, five-arm, randomised controlled trial in Bangladesh. We recruited healthy infants aged 6 weeks at 42 immunisation clinics and randomly assigned them (with blocks of 15, three per group) to receive a short three-dose schedule of bOPV (bOPV short) or mOPV1 (mOPV1 short) with the first dose given at age 6 weeks, the second at age 8 weeks, and the third at age 10 weeks; or to a standard three-dose schedule of bOPV (bOPV standard) or mOPV1 (mOPV1 standard) or trivalent OPV (tOPV standard) with the first dose given at age 6 weeks, the second at 10 weeks, and the third at age 14 weeks. The primary outcome was the proportion of infants with antibody seroconversion for type 1, type 2, and type 3 polioviruses. The primary, modified intention-to-treat analysis included all patients who had testable serum samples before and after receiving at least one OPV dose. We used a 10% margin to establish non-inferiority for bOPV groups versus mOPV1 groups in seroconversion for type 1 poliovirus, and for bOPV1 short versus bOPV1 standard for types 1 and 3. This trial is registered at ClinicalTrials.gov, number NCT01633216, and is closed to new participants. Findings Between May 13, 2012, and Jan 21, 2013, we randomly assigned 1000 infants to our study groups. 927 completed all study visits and were included in the primary analysis. Seroconversion for type-1 poliovirus was recorded in 183 (98%, 95% CI 95–100) of 186 infants given bOPV short, 179 (97%, 94–99) of 184 given bOPV standard, 180 (96%, 92–98) of 188 given mOPV short, 178 (99%, 97–100) of 179 given mOPV1 standard, and 175 (92%, 87–96) of 190 given tOPV standard. Seroconversion for type 2 was noted in 16 infants (9%, 5–14) on bOPV short, 29 (16%, 11–22) on bOPV standard, 19 (10%, 7–15) on mOPV short, 33 (18%, 13–25) on mOPV1 standard, and 182 (96%, 92–98) on tOPV standard. Seroconversion for type 3 was noted in 175 infants (94%, 90–97) on bOPV short, 176 (96%, 92–98) on bOPV standard, 18 (10%, 6–15) on mOPV short, 25 (14%, 10–20) on mOPV1 standard, and 167 (88%, 83–92) on tOPV standard. The short schedules for mOPV1 and bOPV elicited a non-inferior antibody response compared with the bOPV standard schedule. 104 adverse events were reported in 100 infants during follow up. 36 of these events needed admission to hospital (32 were pneumonia, two were vomiting or feeding disorders, one was septicaemia, and one was diarrhoea with severe malnutrition). One of the infants admitted to hospital for pneumonia died 5 days after admission. No adverse event was attributed to the vaccines. Interpretation Our trial showed that three doses of mOPV1 or bOPV with a short schedule of 2 week intervals between doses induces an immune response similar to that obtained with the standard schedule of giving doses at 4 week intervals. These findings support the use of these vaccines in campaigns done at short intervals to rapidly increase population immunity against polioviruses to control outbreaks or prevent transmission in high-risk areas. Funding Centers for Disease Control and Prevention and UNICEF.